Computer Aided Verification - Ruzica Piskac; Zvonimir Rakamarić (Springer Nature Switzerland, 2025)
This open access 4-volume set constitutes the proceedings of the 37th International Conference on Computer Aided Verification, CAV 2025, held in Zagreb, Croatia, in July 23-25, 2025. The 51 regular papers are presented, together with 24 tool papers and 4 case-study papers, were carefully reviewed and selected from 305 submissions. The accepted papers cover a wide spectrum of topics, from theoretical results to applications of formal methods. These papers apply or extend formal methods to a wide range of domains such as concurrency, machine learning and neural networks, quantum systems, as well as hybrid and stochastic systems.